Remanagement of Singlet and Triplet Excitons in Single-Emissive-Layer Hybrid White Organic Light-Emitting Devices Using Thermally Activated Delayed Fluorescent Blue Exciplex - Liu, Xiao-Ke; Chen, Zhan; Qing, Jian; Zhang, Wen-Jun; Wu, Bo; Tam, Hoi Lam; Zhu, Furong; Zhang, Xiao-Hong; Lee, Chun-Sing (Advanced materials (Weinheim), 2015)
A high‐performance hybrid white organic light‐emitting device (WOLED) is demonstrated based on an efficient novel thermally activated delayed fluorescence (TADF) blue exciplex system. This device shows a low turn‐on voltage of 2.5 V and maximum forward‐viewing external quantum efficiency of 25.5%, which opens a new avenue for achieving high‐performance hybrid WOLEDs with simple structures.